Effect of extraction methods with different matrix for gelatin recovery and properties: a review - Ee, S. C.; Bakar, Jamilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Gelatin is one of the most versatile and unique hydrocolloid ingredient widely used in food industries, serving multiple functions in food system such as emulsifier, foaming agent, encapsulating agent, colloid stabilizer and film-forming ability among others. These advantages led to the continuous exploration of new source of gelatin as well as optimization of the extracting conditions of gelatin. Major commercial production of gelatin are from the skin and bones of porcine and bovine (mammalian gelatin) and the rest are from non-mammalian sources such as fish, which are still far behind the porcine and bovine in terms of production. Poultry derived gelatin is growing in importance as new potential mammalian gelatin source. The current article entails an overview of recent research in extraction of gelatin from different matrixs using alkaline, acid, enzymatic aided extraction and these selected methods affect the functional properties of the extracted gelatin. Various enzymes used to improve the physicochemical properties such as bloom strength, thermal properties, solubility and pH stability of gelatin of gelatin are also discussed.